KARAKTERISTIK ORGANOLEPTIK DAN CEMARAN YOGHURT SINBIOTIK UBI UNGU DAN SUSU SEGAR - Fitriyah, Dina; Jannah, Miftahul; Ayu, Dessya Putri; Werdiharini, Agustina Endah; Warsito, Heri; Ratri, Putri Rahayu (Pasundan Food Technology Journal (PFTJ), 2025)
Purple sweet potato synbiotic yogurt is a synbiotic drink that utilizes local food and is beneficial for health. The synbiotic purple sweet potato yoghurt is expected to enhance the functional value of yoghurt as a probiotic and increase the utilization value of purple sweet potatoes. Nevertheless, yoghurt with the addition of other food ingredients must still meet the standard quality requirements for yoghurt. The purpose of this study was to analyze the organoleptik and contamination of pathogen bacteria and heavy metal. This study used an experimental design with the development of 4 formulations with a ratio of fresh milk and purple sweet potato extract, namely 1: 4 (P1), 2: 3 (P2), 3: 2 (P3), 4: 1 (P4). Purple sweet potato synbiotic yogurt and fresh milk were subjected to organoleptic tests on 30 untrained panelists, microbiological contamination and heavy metal contamination. The results showed that on average panelists liked the P4 formula based on the characteristics of taste, aroma and texture, and liked the P3 formula based on the characteristics of color. Contamination test showed negative contamination of Salmonella, coliform, and L. monocytogenes and no contamination of Hg, Pb, Sn was detected. Cu contamination of 0.19 is still below the standard. The synbiotic yoghurt made from purple sweet potato and fresh milk was generally well accepted by the panelists, and contamination levels, it is complied with SNI standard.